'Poverty, gender and old age in the Victorian and Edwardian workhouse'. (December 2022) - Williams, Samantha
Abstract: The workhouse was a central facet of the new poor law and the elderly – and aged men in particular – came to dominate workhouse populations. This article is the first to analyse a very large data set of almost 4, 000 workhouses from all areas of England and Wales extracted from the I-CeM data set, which reveals the composition of workhouse residents on census night by age, gender, and geography between 1851 and 1911. Factors influencing the proportion of the elderly in the workhouse include the dependency ratio and internal migration, urbanisation and a commitment to institutions in cities, and the availability of outdoor relief and other avenues of support. Destitution, want of work, old age and illness propelled the elderly into the workhouse. The crusade against outrelief of the 1870s contributed to this increase, and, while the introduction of old age pensions reduced those over the age of 70, this did not prevent the 'younger aged' (those aged 60–69) from increasing.